2011
DOI: 10.3746/jkfn.2011.40.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Human Colon Carcinoma HCT116 Cells Using a Water Extract of Lepidium virginicum L.

Abstract: To examine the anti-cancer effects of Lepidium virginicum L., the anti-proliferative and pro-apoptotic effects of a water extract of L. virginicum leaves (WELVL) and of L. virginicum roots (WELVR) were investigated in HCT116 human colon carcinoma cells. The treatment of HCT116 cells with WELVL and WELVR resulted in the inhibition of growth and morphological changes in a concentration-dependent manner by inducing apoptosis. The growth inhibition and apoptosis induction by WELVR was stronger than that of WELVL t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Colon cancer is of particular interest in South Korea, as its prevalence has increased with the adaptation of Western eating habits (1,2). Previous studies have shown that various plant extracts have anti-cancer effects and cause apoptosis of HCT116 colon cancer cells (4,(26)(27)(28). The present study investigated the apoptotic effects of an extract of the fruit of Cnidium monnieri (L.) Cusson, based on previous studies (23,25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Colon cancer is of particular interest in South Korea, as its prevalence has increased with the adaptation of Western eating habits (1,2). Previous studies have shown that various plant extracts have anti-cancer effects and cause apoptosis of HCT116 colon cancer cells (4,(26)(27)(28). The present study investigated the apoptotic effects of an extract of the fruit of Cnidium monnieri (L.) Cusson, based on previous studies (23,25).…”
Section: Discussionmentioning
confidence: 97%
“…Caspase-9, in turn, is activated through cytochrome-C release due to the activation of Bax and Bak (19,22). When HCT116 colon cancer cells were treated with corosolic acid or Lepidium virginicum L. extract, pro-caspase-3 and Bcl-2 expression were decreased and Bax expression was increased (27,28). Pro-caspase-3 expression was also shown to be decreased by curcumin or Dorema glabrum seed extract (26,31).…”
Section: A B a Bmentioning
confidence: 99%
“…The water extract of L. virginicum (LV) contains anti-cancer and anti-in ammatory properties. Additionally, the presence of benzyl glucosinolate in this extract also exerts a bacteriostatic function [8,9]. L. meyenii (LM), on the other hand, contains not only rich nutrition, but also plenty of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%